2007
DOI: 10.1086/510999
|View full text |Cite
|
Sign up to set email alerts
|

Transience of Hot Dust around Sun‐like Stars

Abstract: There is currently debate over whether the dust content of planetary systems is stochastically regenerated or originates in planetesimal belts evolving in quasi-steady state. In this paper a simple model for the steady state evolution of debris disks due to collisions is developed and confronted with the properties of the emerging population of 7 sun-like stars that have hot dust at < 10 AU. The model shows that there is a maximum possible disk mass at a given age, since more massive primordial disks process t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
586
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 354 publications
(622 citation statements)
references
References 59 publications
(88 reference statements)
35
586
1
Order By: Relevance
“…While f 12gi is not well known, it can be said to be constrained to be less than 100 %. One might be mistaken for thinking that this is close to 100 % from the literature, since mid-IR emission is usually interpreted as the result of giant impacts, but there are not many cases where it is possible to rule out that the dust is simply the bottom end of the collisional cascade of a massive asteroid belt, at least for systems that are in this age range for which collisional processes have yet to have a significant effect on depleting any remnant asteroid belt (Wyatt et al 2007a).…”
Section: How Common Are Late Giant Impacts?mentioning
confidence: 92%
See 1 more Smart Citation
“…While f 12gi is not well known, it can be said to be constrained to be less than 100 %. One might be mistaken for thinking that this is close to 100 % from the literature, since mid-IR emission is usually interpreted as the result of giant impacts, but there are not many cases where it is possible to rule out that the dust is simply the bottom end of the collisional cascade of a massive asteroid belt, at least for systems that are in this age range for which collisional processes have yet to have a significant effect on depleting any remnant asteroid belt (Wyatt et al 2007a).…”
Section: How Common Are Late Giant Impacts?mentioning
confidence: 92%
“…(1) and assuming that all the debris is in fragments of the same size. While more accurate calculations are readily available (see Wyatt et al 2007a), this illustrates how the collisional depletion rate is proportional to the mass of largest fragments. This leads to the mass remaining constant until the largest objects have come to collisional equilibrium, following which the mass decays inversely with time, with dynamical processes further accelerating the depletion process.…”
Section: Collisional Evolutionmentioning
confidence: 99%
“…During the inside-out stirring, different annular regions in a disk brighten up and enter their erosive debris disk phase. Their individual fractional luminosities decay more slowly than 1/t (Dominik & Decin 2003;Wyatt et al 2007;Trilling et al 2008;Löhne et al 2008). However, this decay is even more rapid than the outward migration of the stirring front.…”
Section: Disk Evolutionmentioning
confidence: 99%
“…For example, dust has been detected from well within one AU (Beichman et al 2005;Absil et al 2006), out to hundreds of AU (e.g., Su et al 2005). While the former cases seem to be rare (Wyatt et al 2007), the latter are more commonly reported, corresponding to significantly higher detection rates at longer wavelengths. In addition, from a purely observational point of view, a huge population of fairly massive, but cold disks A&A 537, A110 (2012) could still be hidden below current sensitivity limits.…”
Section: Introductionmentioning
confidence: 99%
“…While the ALMA observations were best suited to outer regions analogous to evolved Kuiper belt analogs, the Herschel data were uniquely sensitive to an evolved, asteroid-like belt at G29-38 and in general to dust at temperatures and orbital regions intermediate to the relatively warm dust seen at polluted white dwarfs and the cooler dust often detected at main sequence stars. The non-detection at G29-38 is not wholly unexpected, as disk evolution models supported by observations of main sequence stars predict that the available mass in both dust and parent bodies decreases significantly over timescales of several hundred Myr (Wyatt et al 2007), and this depletion is likely enhanced during the post-main sequence (Bonsor & Wyatt 2010).…”
Section: Discussionmentioning
confidence: 65%